ChemInform Abstract: Self‐Monitoring of Tear Glucose: The Development of a Tear Based Glucose Sensor as an Alternative to Self‐Monitoring of Blood Glucose. Issue 37 (August 2016) - La Belle, Jeffrey T.; Adams, Anngela; Lin, Chi‐En; Engelschall, Erica; Pratt, Breanna; Cook, Curtiss B.
Abstract: Review: 43 refs.